2018
DOI: 10.7717/peerj.5294
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ and IL-5 whole blood response directed against mycolactone polyketide synthase domains in patients withMycobacterium ulceransinfection

Abstract: BackgroundBuruli ulcer is a disease of the skin and soft tissues caused by infection with a slow growing pathogen, Mycobacterium ulcerans. A vaccine for this disease is not available but M. ulcerans possesses a giant plasmid pMUM001 that harbours the polyketide synthase (PKS) genes encoding a multi-enzyme complex needed for the production of its unique lipid toxin called mycolactone, which is central to the pathogenesis of Buruli ulcer. We have studied the immunogenicity of enzymatic domains in humans with M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 35 publications
(41 reference statements)
0
13
0
Order By: Relevance
“…Twelve original research studies met the inclusion criteria ( Fig 1 and Table 1), with the earliest from 1952 [25] and the most recent from a WHO conference abstract in 2019 presented by Avumegah [8], which was also Table 1 has been adapted from PhD thesis available online [26]. List of abbreviations not in text: Acyl carrier protein 2& 3(ACP2, ACP3); Acyltransferase with acetate specificity type 1 &2 (ATac1, ATac2); Acyltransferase with propionate specificity (ATp); Enoylreductase (ER); Ketoreductase type A and B (KRA, KR B); Ketosynthase type C (KS C); Ketosynthase domain (Ksalt), dehydratase (DH), and Phorbol 1-myristate 1-acetate (PMA) [34]. Cluster of differentiation 4 (CD4); CD 40 Ligand (CD40L); Tumor necrosis factor alpha (TNFα) [32].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve original research studies met the inclusion criteria ( Fig 1 and Table 1), with the earliest from 1952 [25] and the most recent from a WHO conference abstract in 2019 presented by Avumegah [8], which was also Table 1 has been adapted from PhD thesis available online [26]. List of abbreviations not in text: Acyl carrier protein 2& 3(ACP2, ACP3); Acyltransferase with acetate specificity type 1 &2 (ATac1, ATac2); Acyltransferase with propionate specificity (ATp); Enoylreductase (ER); Ketoreductase type A and B (KRA, KR B); Ketosynthase type C (KS C); Ketosynthase domain (Ksalt), dehydratase (DH), and Phorbol 1-myristate 1-acetate (PMA) [34]. Cluster of differentiation 4 (CD4); CD 40 Ligand (CD40L); Tumor necrosis factor alpha (TNFα) [32].…”
Section: Resultsmentioning
confidence: 99%
“…A summary of these 12 studies are presented in Table 1. Nine out of the 12 CMI and/or serological studies identified were conducted in Africa, specifically Benin [14], Cameroon [31], Cote d'Ivoire [29], Zaire (now Democratic Republic of Congo, DRC) [27], Ghana [15,19,[30][31][32]34] and Uganda [27]. The remaining three studies, were conducted in Australia [8,26,28].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations